2022
DOI: 10.1002/jper.21-0443
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of Er,Cr:YSGG laser therapy used as an adjunct to non‐surgical treatment of periodontitis: Twelve‐month results from a pilot study

Abstract: Background:The purpose of this study was to evaluate the results of adjunctive Er,Cr:YSGG laser therapy with scaling and root planing (SRP) as compared with SRP alone in the treatment of moderate to severe periodontitis. Methods: Fifteen adults (aged 27 to 65 years) with 90 nonadjacent sites probing ≥ 5 mm were treated in split-mouth design with SRP and laser therapy versus SRP alone. Probing pocket depth (PPD), gingival recession (GR), clinical attachment level (CAL), plaque, and bleeding on probing were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…On the contrary, a recent study by Klokkevold et al, carried out on a sample of 15 adults with 90 nonadjacent sites probing ≥ 5 mm, assessed PPD, CAL, BOP, PI, and GR at 1, 3, 6, 9, and 12 month intervals and concluded that adjunctive Er,Cr:YSGG laser therapy with SRP provides clinical improvement in the treatment of moderate-severe periodontitis similar to that of SRP alone and may offer some advantage for deeper (≥7 mm) pockets. This is contrary to our findings: at the 6- and 12-month time points (T2 and T3), the values recorded for all indicators were significantly better for the laser group [ 51 ].…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, a recent study by Klokkevold et al, carried out on a sample of 15 adults with 90 nonadjacent sites probing ≥ 5 mm, assessed PPD, CAL, BOP, PI, and GR at 1, 3, 6, 9, and 12 month intervals and concluded that adjunctive Er,Cr:YSGG laser therapy with SRP provides clinical improvement in the treatment of moderate-severe periodontitis similar to that of SRP alone and may offer some advantage for deeper (≥7 mm) pockets. This is contrary to our findings: at the 6- and 12-month time points (T2 and T3), the values recorded for all indicators were significantly better for the laser group [ 51 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, their procedural approach seemed to not be clinically practical and therefore not appropriate for consideration in the present study. On the other hand, quite recently, Klokkevold et al 47 . performed an RCT study for the initial active treatment of moderate to severe pockets using an Er,Cr:YSGG laser with a strategy quite similar to the present study.…”
Section: Discussionmentioning
confidence: 77%